Development of ROPUTRAS Games in Group Guidance to Foster Self-Awareness among MTs Al-Islam Students - Gustama, Rosyid Arfan; Rahman, Diniy Hidayatur; Setiyowati, Arbin Janu (Indonesian Journal of Counseling and Development, 2025)
One of the periods of growth and development that individuals will face is adolescence. Adolescence can be referred to as a period of identity search, where adolescents are required to develop self-awareness. This is especially true for students, who live their lives according to strong Islamic and social values. Students with low self-awareness face difficulties in daily life, struggling to recognize and reflect on their strengths. In addition, violations of the cottage such as leaving during class time, choosing to go to the canteen during class time and smoking behavior in the canteen are still widely seen. The purpose of this study is to develop the ROPUTRAS (Spinning Wheel of students Self-Awareness) game as a tool to enhance self-awareness among MTs students. The research and development procedure adopts the ADDIE model, implemented in five stages: analysis, design, development, implementation, and evaluation. The results of expert and potential user evaluations were analyzed using the Inter-rater-agreement method. Additionally, the effectiveness test used the Wilcoxon signed-rank test analysis. Based on the validation results by subject matter experts, media experts, and potential users, it can be concluded that this guide has very high validity, referring to the aspect of acceptability. Therefore, it can be concluded that the ROPUTRAS game media product for developing self-awareness among MTs students is suitable for use. In addition, violations of the cottage such as leaving during class time, choosing to go to the canteen during class time and smoking behavior in the canteen are still widely seen.